Functional interrogation of a SARS-CoV-2 host protein interactome identifies unique and shared coronavirus host factors - Hoffmann, Hans-Heinrich; Sánchez-Rivera, Francisco J.; Schneider, William M.; Luna, Joseph M.; Soto-Feliciano, Yadira M.; Ashbrook, Alison W.; Le Pen, Jérémie; Leal, Andrew A.; Ricardo-Lax, Inna; Michailidis, Eleftherios; Hao, Yuan; Stenzel, Ansgar; et al. (Cell host and microbe, 2021)
The ongoing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has devastated the global economy and claimed more than 1.7 million lives, presenting an urgent global health crisis. To identify host factors required for infection by SARS-CoV-2 and seasonal coronaviruses, we designed a focused high-coverage CRISPR-Cas9 library targeting 332 members of a recently published SARS-CoV-2 protein interactome. We leveraged the compact nature of this library to systematically screen SARS-CoV-2 at two physiologically relevant temperatures along with three related coronaviruses (human coronavirus 229E [HCoV-229E], HCoV-NL63, and HCoV-OC43), allowing us to probe this interactome at a much higher resolution than genome-scale studies. This approach yielded several insights, including potential virus-specific differences in Rab GTPase requirements and glycosylphosphatidylinositol (GPI) anchor biosynthesis, as well as identification of multiple pan-coronavirus factors involved in cholesterol homeostasis. This coronavirus essentiality catalog could inform ongoing drug development efforts aimed at intercepting and treating coronavirus disease 2019 (COVID-19) and help prepare for future coronavirus outbreaks.
Available online 16 December 2020
Gesehen am 10.05.2021